Prevalence and factors associated with the mental health status of elderly in the Matara Municipal Council area - Gunaratna, I.E (My University, 2009)
A response rate of 92.1 percent led to the participation or 515 elders. Nearly hall' the participants were between age 60-64 years and the majority was females. One third of the study population was widows, where widows were significantly higher than widowers. More than hall the sample had educational level above grade live. Majority (95 percent ) were able to carry out activities or daily living but the percentage of impairment for instrumental activities of daily living were higher (20 percent ). Establishment of a system to identify mental illnesses 01' the elderly 1'01' treatment and treatment and referral at curative care institutions, encouragement of people to adopt practices like living with the spouse, living in a house owned by self or spouse, having a separate room to live and having regular visits by friends and relatives. provision of legal advice with regard to transfer of property to the children. promotion of activities like rearing pets, . doing gardening, watching television and engaging in voluntary social and aesthetic activities through community based elders committees and community centers of local government bodies, encouragement of younger generation to have savings during their economical) active life years and invest on 'insurance policies and organizing behavior change programmes on active ageing which includes positive thinking and being satisfied with is available are suggested to face this situation